2002
DOI: 10.1038/nature00775
|View full text |Cite
|
Sign up to set email alerts
|

Marine aerosol formation from biogenic iodine emissions

Abstract: The formation of marine aerosols and cloud condensation nuclei--from which marine clouds originate--depends ultimately on the availability of new, nanometre-scale particles in the marine boundary layer. Because marine aerosols and clouds scatter incoming radiation and contribute a cooling effect to the Earth's radiation budget, new particle production is important in climate regulation. It has been suggested that sulphuric acid derived from the oxidation of dimethyl sulphide is responsible for the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
652
4
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 737 publications
(688 citation statements)
references
References 26 publications
11
652
4
2
Order By: Relevance
“…[4] The formation of ultra-fine particles in the coastal atmosphere has been observed frequently [O'Dowd et al, 1998[O'Dowd et al, , 2002O'Dowd and Hoffmann, 2005]. Positive correlations between seaweed mass, I 2 emissions and the resulting particle concentrations have been elucidated from chamber experiments [Sellegri et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…[4] The formation of ultra-fine particles in the coastal atmosphere has been observed frequently [O'Dowd et al, 1998[O'Dowd et al, , 2002O'Dowd and Hoffmann, 2005]. Positive correlations between seaweed mass, I 2 emissions and the resulting particle concentrations have been elucidated from chamber experiments [Sellegri et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another important role for RHS has been proposed. On the basis of a variety of laboratory studies it has been suggested that photochemical production of condensable iodine oxides is responsible for the formation of ultrafine particles in the coastal environment [Hoffmann et al, 2001;O'Dowd et al, 2002a]. Such a mechanism could explain the recent observations of bursts of new particles at low tide in the coastal atmosphere [O'Dowd et al, 1998] and has the potential to make an important contribution to the Earth's radiative budget.…”
Section: Introductionmentioning
confidence: 99%
“…While Clarke et al (1998) found evidence for particle production linked to high DMS emissions in the Pacific, a more robust analysis of particle production from H 2 SO 4 by Pirjola et al (2000) pointed out that while binary nucleation was likely to occur in the polar regions, and ternary nucleation likely to occur in many other marine environments, there is typically insufficient H 2 SO 4 vapour to contribute to growth of stable clusters into aerosol particles (operationally defined as particles with DO3 nm). O'Dowd et al (2002a) demonstrated that unless newly formed stable clusters can grow sufficiently fast, the clusters are scavenged by the preexisting aerosol coagulation sink. For example, a 1 nm particle, under typical H 2 SO 4 concentrations, will grow by condensation of H 2 SO 4 vapour at a rate of 0.5!10 K4 nm s K1 .…”
Section: Introductionmentioning
confidence: 99%